Terminologia e tradução juramentada: questões de tipologia textual e equivalência terminológica interlinguística Português-francês-italiano - Barros, Lidia Almeida [UNESP] (2010)
In this study we analyse a body of documents in sworn translation from and to Portuguese in relation to French and Italian. Our objective has been to check the textual typology most requested for sworn translation in these languages and to outline a profile of the terminology recurrent in these types of text. We also present examples of interlinguistic terminological equivalence which become apparent when one translates some of the types of text in our corpus. The data presented here was obtained by the LexTraJu-O lexical project of sworn translation, of which the research is developed in the São José do Rio Preto campus of UNESP with the objective of obtaining resources for the improvement of the Translation Courses of this institution and of making a contribution to translation studies on the theme of sworn translation.